2012
DOI: 10.1590/s0101-60832012000600003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de depressão em usuários de unidades de atenção primária

Abstract: Resumo Contexto: A depressão é um importante problema de saúde global e vem causando impacto negativo na vida dos indivíduos e na de suas famílias, além de elevar a demanda dos serviços de saúde. Objetivo: Verificar a prevalência de depressão e de fatores associados em indivíduos com idade superior a 14 anos que buscaram atendimento na atenção primária. Métodos: Estudo transversal em três Unidades Básicas de Saúde vinculadas à Universidade Católica de Pelotas. A depressão, os transtornos de ansiedade e o risco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
52

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 30 publications
2
12
0
52
Order By: Relevance
“…A study conducted in a medical unit of a university hospital involving people with suicidal ideation showed significantly higher rates of moderate and severe depressive disorders (22) . A study on the prevalence of depression in the primary health care, associating it with abuse, alcohol addiction and suicide risk, found that people presenting suicide risk had a 2.5 higher chance of depression than those without risk of suicide (23) . Family conflict is also in the literature as a decisive factor for suicidal behavior among drug addicts.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in a medical unit of a university hospital involving people with suicidal ideation showed significantly higher rates of moderate and severe depressive disorders (22) . A study on the prevalence of depression in the primary health care, associating it with abuse, alcohol addiction and suicide risk, found that people presenting suicide risk had a 2.5 higher chance of depression than those without risk of suicide (23) . Family conflict is also in the literature as a decisive factor for suicidal behavior among drug addicts.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of depression in the general population can range from 11 to 18.4%, 24 and can reach 23%, 25 among people who have another chronic disease, and 23.9%, 26 in patients treated in primary health care. Among the elderly, the prevalence of depression reaches approximately 20% among noninstitutionalized people.…”
Section: Discussionmentioning
confidence: 99%
“…Contrariamente ao veri cado na literatura (Keyes, 2007) os indivíduos que não frequentam a rede de cuidados de saúde são os que relatam níveis mais elevados de depressão, ansiedade e stress, podendo este resultado dever-se ao facto de os participantes, tendo em conta as pontuações mínimas e máximas possíveis do instrumento utilizado, apresentarem níveis relativamente baixos de depressão. Os indivíduos com o ensino básico revelam níveis mais elevados de depressão, o que vai de encontro ao estudo de Molina et al, (2012), que defendem que a baixa escolaridade, entre outros fatores, pode estar associada a níveis mais elevados de depressão, devido às condições de vida e ao maior número de stressores ambientais. Os jovens mais velhos também relatam níveis mais elevados de depressão sendo que Bayram e Bilgel (2008) referem que a transição para a idade adulta representa um período de risco para o aparecimento de ansiedade.…”
Section: Discussionunclassified